2013
DOI: 10.18061/emr.v8i3-4.3942
|View full text |Cite
|
Sign up to set email alerts
|

Musical Objects, Cross-Domain Correspondences, and Cultural Choice: Commentary on “Cross-Cultural Representations of Musical Shape” by George Athanasopoulos and Nikki Moran

Abstract: The target article illustrates deep cross-cultural gaps, involving not only the representation of musical shape but also the notion of a musical object itself. Yet, numerous empirical findings suggest that important cross-modal correspondences involving music and visual dimensions are inborn or learned at infancy, prior to the acquisition of language and most culture-specific behavior. Drawing on recent empirical work, the commentary attempts to reconcile this apparent disparity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…We chose the expression “represent sound gesturally” over instructions emphasizing a more communicative aspect of the gestures, e.g., “while listening to the music, move to it in an appropriate way, such that another child could recognize the music while watching your movements without sound” (Kohn and Eitan, 2009 ) or, pertaining to sound drawings, asking participants to “represent the sound on paper in such a way that if another member of their community saw their marks they should be able to connect them with the sound” (Athanasopoulos and Moran, 2013 ). Although constituting seemingly negligible differences in instruction, the resulting drawings and gestures may give rise to different outcomes, particularly in a cross-cultural context as discussed by Eitan ( 2013b ).…”
Section: Discussionmentioning
confidence: 99%
“…We chose the expression “represent sound gesturally” over instructions emphasizing a more communicative aspect of the gestures, e.g., “while listening to the music, move to it in an appropriate way, such that another child could recognize the music while watching your movements without sound” (Kohn and Eitan, 2009 ) or, pertaining to sound drawings, asking participants to “represent the sound on paper in such a way that if another member of their community saw their marks they should be able to connect them with the sound” (Athanasopoulos and Moran, 2013 ). Although constituting seemingly negligible differences in instruction, the resulting drawings and gestures may give rise to different outcomes, particularly in a cross-cultural context as discussed by Eitan ( 2013b ).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests the association between pitch and vertical space in congenital amusics may not be as stable as that in control individuals. On the other hand, it has been suggested that language can strengthen pre-existing associations between pitch and space (Dolscheid, Shayan, Majid, & Casasanto, 2013;Eitan, 2013). Thus, one possibility is that amusic individuals rely on semantic labels to link pitch with spatial location, and this reliance consumes additional processing time.…”
Section: Discussionmentioning
confidence: 99%